Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13071-020-04345-2
|View full text |Cite
|
Sign up to set email alerts
|

New vectors in northern Sarawak, Malaysian Borneo, for the zoonotic malaria parasite, Plasmodium knowlesi

Abstract: Background Plasmodium knowlesi is a significant cause of human malaria in Sarawak, Malaysian Borneo. Only one study has been previously undertaken in Sarawak to identify vectors of P. knowlesi, where Anopheles latens was incriminated as the vector in Kapit, central Sarawak. A study was therefore undertaken to identify malaria vectors in a different location in Sarawak. Methods Mosquitoes found landing on humans and resting on leaves over a 5-day period at two sites in the Lawas District of northern Sarawak w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 67 publications
(112 reference statements)
2
23
0
Order By: Relevance
“…With regards to the detection of Plasmodium , observations including a higher sporozoite rate in vectors compared to other studies 8 , 9 , 11 , 13 15 ; discrepancy between PCR and sequencing results, and the presence of Plasmodium species which could not be detected with the primers specific for the five simian malaria parasites that are reported in the current study, are consistent with the observations from our previous study in Lawas, Sarawak 18 . We have suggested that the high sporozoite rates observed could be attributed to a higher sensitivity of the sampling and detection methods since we used all the salivary glands for DNA extraction and we detected Plasmodium with molecular methods.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…With regards to the detection of Plasmodium , observations including a higher sporozoite rate in vectors compared to other studies 8 , 9 , 11 , 13 15 ; discrepancy between PCR and sequencing results, and the presence of Plasmodium species which could not be detected with the primers specific for the five simian malaria parasites that are reported in the current study, are consistent with the observations from our previous study in Lawas, Sarawak 18 . We have suggested that the high sporozoite rates observed could be attributed to a higher sensitivity of the sampling and detection methods since we used all the salivary glands for DNA extraction and we detected Plasmodium with molecular methods.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the sequences generated in our study did not fall into any particular clade following phylogenetic analysis and the reasons for this could be either that the SSUrRNA gene is not a suitable marker for identification of species of Plasmodium or that there are species of Plasmodium circulating among wildlife in Betong and Lawas that have not previously been characterised 18 . It would be necessary to sequence additional genes in order to confirm that there are novel species of Plasmodium carried by these mosquitoes as was done recently with non-nuclear genes 5 .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations